Does Intellectual Capital Have A Moderating Role in The Association Between Tax Avoidance and Firm Value? - Raja Pranatha Doloksaribu; Farhan Hadiantoro; Amrie Firmansyah (SUBSTANSI, 2022)
This study examines the effect of companies' tax avoidance on firm value by using intellectual capital as a moderating variable during the Covid-19 pandemic. The sample for this study used companies in the consumer goods industry sector listed on the IDX during the Covid-19 pandemic. The secondary data is sourced from the company's financial and annual reports for 2020 and 2021. The sample was determined using the purposive sampling method with 52 samples. The study results show that the company's tax avoidance during the Covid-19 pandemic did not affect the firm value. This study also concludes that the intellectual capital owned by the company does not moderate the effect of tax avoidance on firm value. This research indicates that investors in Indonesia only consider the profitability performance of companies in investing during the Covid-19 pandemic.